Comparison of enzymatic and nonenzymatic sensors for cholesterol detection - Derina K. V. Kseniya Vladimirovna; Chulkova I. V. Irina Vasilievna; Dorozhko E. V. Elena Vladimirovna; Tayshibekova E. K. Ekaterina Karimovna; Korotkova E. I. Elena Ivanovna (2015, 2015)
Заглавие с экрана